2004
DOI: 10.1097/01.asn.0000135055.61833.a8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Angiotensin II and NF-κB–Dependent Pathways in Modulating Macrophage Infiltration in Experimental Diabetic Nephropathy

Abstract: Abstract. NF-B-dependent pathways play an important role in macrophage infiltration and kidney injury. NF-B is regulated by angiotensin II (AII). However, the role of this pathway in diabetic nephropathy has not been clearly delineated. First, the activation of NF-B, monocyte chemoattractant protein-1 (MCP-1), and macrophage infiltration in the diabetic kidney were explored, in a temporal manner. The active subunit of NF-B, p65, was elevated in the diabetic animals in association with increased MCP-1 gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 43 publications
7
117
0
4
Order By: Relevance
“…NF-B is composed of p50 and p65 subunits, among which p65 is a potent transcriptional activator, strongly promoting inflammatory reaction in kidney diseases (40). In this study, marked activation of p65, not p50, was closely correlated with the renal inflammation, consistent with the previous observation in experimental diabetic nephropathy (41). A putative NF-B regulatory site has been found in the mouse Smad7 promoter, suggesting a functional link between the NF-B and Smad7 (42).…”
Section: Discussionsupporting
confidence: 80%
“…NF-B is composed of p50 and p65 subunits, among which p65 is a potent transcriptional activator, strongly promoting inflammatory reaction in kidney diseases (40). In this study, marked activation of p65, not p50, was closely correlated with the renal inflammation, consistent with the previous observation in experimental diabetic nephropathy (41). A putative NF-B regulatory site has been found in the mouse Smad7 promoter, suggesting a functional link between the NF-B and Smad7 (42).…”
Section: Discussionsupporting
confidence: 80%
“…Oxidative-nitrosative stress triggers several important downstream mechanisms, i.e., activation of mitogen-activated protein kinases [20,27], the nuclear transcription factor NF-κB [28,29], and upregulation of growth factors such as transforming growth factor-β (TGF-β) [14,15], cytokines [30,31], and vascular endothelial growth factor [32] implicated in diabetic renal disease [12,[27][28][29]33,34]. In vitro and in vivo studies in nondiabetic models of oxidative injury as well as animal and cell culture models of diabetic complications revealed that free radical and peroxynitrite-induced DNA single-strand breakage is also responsible for activation of the nuclear enzyme poly (ADP-ribose) polymerase (PARP) and resultant energy failure, profound metabolic imbalances, and changes in transcriptional regulation and gene expression [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant regulation of NF-B may result in inflammatory and autoimmune diseases, impair antiviral immune responses, and contribute to malignant cellular transformation. 1-3 Activation of NF-B, with subsequent production of cytokines, chemokines, and adhesion molecules, is an important component of the pathogenesis of several forms of renal disease, including diabetic nephropathy (DN), 4,5 hypertensive nephrosclerosis (HN), 6,7 IgA nephropathy (IgAN), 8 membranous glomerulopathy, 9 and HIV-associated nephropathy. 10 -12 The canonical NF-B activation pathway can be induced by a variety of stimuli, including TNF-␣.…”
mentioning
confidence: 99%